Hypermedia cat encyclopedia for children - Siti Hanisah, Majid (2011)
Creating courseware as a learning tool is one of the common way to ease the learning process of the targeted user and the people that using the application.Hypermedia Cats Encyclopedia for Children (HCEC) is developed as a standalone application and the targeted user is the twelve years old children to encourage them in learning about the animal especially cats and for the children that loves to read and can use this application and help them from bringing the bulky encyclopedia book.This application can help the children in their learning process and allure them to have the passion in reading.This application is fbcusing on implementing Human Computer Interaction (HC1) strategies with its heuristics and combine with specific. golden rules from Shneiderman that related with the application for the children.Rapid Application Development(RAD) is a development lifecycie designed to give much faster development and higher quality results than those achieved with the traditional lifecycle.That is the main factor that this type of methodology is chosen to develop this application though these two semesters.